Sleep as a default state of cortical and subcortical networks. Issue 15 (June 2020) - Bandarabadi, Mojtaba; Vassalli, Anne; Tafti, Mehdi
Abstract : Sleep has been conceptualized as 'activity-dependent', hence a response to prior waking experience, and proposed to be 'the price the brain pays for plasticity during wakefulness'. We here propose that at the level of neuronal networks, particularly those arising from isolated embryonic thalamocortical cells maintained in culture, it represents a default mode of functioning. We show that cell assemblies in ex vivo cultures express powerful sleep specific patterns of oscillatory activity, as well as metabolic and molecular signatures of the sleep state. We summarize recent evidences that support our hypothesis and discuss potential applications of developing ex vivo sleep models to answer open questions in the field.